Employing Critical Reading Strategy to Promote Students’ High Order Thinking Skills - Ratri Handayani (Pancaran Pendidikan, 2018)
This paper aims to share idea about the use of critical reading to stimulate students’ critical thinking and reading comprehension whether it is for academic purpose or reading for enjoyment, particularly in the foreign language learning. The employment of critical reading will automatically involve students’ high-order thinking Skills. Thus, reading strategies is needed as a way to engage students’ active learning during teaching and learning in a reading class. Later on, the beneficial employment of critical reading can be seen from the students’ writing activity of an article critique or a literature review. Student-centered learning is chosen as the teaching method during the reading class. It is believed that students are willingly to get involve, to be active and to be communicative learners. This article will review some previous studies and theory on the employment of critical reading strategy in promoting students’ high order thinking Skills and its effect toward reading comprehension.